2006
DOI: 10.1111/j.1464-410x.2006.06215.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor stimulates embryonic urinary bladder development in organ culture

Abstract: OBJECTIVES To determine whether vascular endothelial growth factor A (VEGF) and its receptors are expressed during bladder development in mice when capillaries are forming, and whether exogenous VEGF might enhance the growth of endothelia and other types of bladder cells, using an embryonic organ‐culture model. MATERIALS AND METHODS Whole bladders from wild‐type mice, at embryonic day (E) 14, were grown in serum‐free organ culture in an air/5% CO2 atmosphere; some cultures were supplemented with VEGF and/or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…As judged by colocalization of Cy5.5 fluorescence with immunofluorescent staining for lineage-specific markers, VEGF receptors and coreceptors in both structures, the tracer preferentially tagged urothelial and neuronal cells, but not vascular or lymphatic endothelial cells. Although there are several reports on immunohistochemical detection of VEGF receptors in urinary bladder (13,14,29), our findings in vivo, for the first time, identify these receptors as accessible and functionally active. Importantly, our findings that in vivo tagged urothelial cells display both VEGF receptors and NRP Fig.…”
Section: Discussionmentioning
confidence: 68%
“…As judged by colocalization of Cy5.5 fluorescence with immunofluorescent staining for lineage-specific markers, VEGF receptors and coreceptors in both structures, the tracer preferentially tagged urothelial and neuronal cells, but not vascular or lymphatic endothelial cells. Although there are several reports on immunohistochemical detection of VEGF receptors in urinary bladder (13,14,29), our findings in vivo, for the first time, identify these receptors as accessible and functionally active. Importantly, our findings that in vivo tagged urothelial cells display both VEGF receptors and NRP Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Although the exact signaling mechanisms between the urothelium and BSMC in culture are unclear, it has been noted previously that soluble growth factors are likely involved. 6,7 Burgu et al demonstrated the importance of vascular endothelial growth factor (VEGF) in the development of murine embryonic bladders in culture. 7 Further, Master et al 6 highlighted the importance of epithelial mesenchymal signaling in the ingrowth of fibroblasts into bladder acellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Burgu et al demonstrated the importance of vascular endothelial growth factor (VEGF) in the development of murine embryonic bladders in culture. 7 Further, Master et al 6 highlighted the importance of epithelial mesenchymal signaling in the ingrowth of fibroblasts into bladder acellular matrix. Therefore to increase cellular penetration, growth factors that are released in culture by the urothelium may be utilized.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridisation using digoxigenin-labelled or radioactive probes was performed on sections as described (Caubit et al, 2005). Probes Embryonic ureter culture and video microscopy E15.5 ureters were dissected and explanted onto platforms (Millipore; pore size 0.4 μm) and cultured in defined, serum-free media, as described for embryonic mouse urinary bladders (Burgu et al, 2006). The timelapse imaging is detailed in the movie legends (see supplementary material).…”
Section: Immunoprobing and In Situ Hybridisationmentioning
confidence: 99%